Flouting Maxim in Creating Humor in Stand-Up Comedy: Comparative Study between Minangkabaunese "Rin Hermana" and American "K-Von" - Jefelia, Fitrisia Yola; Zaim, M (English Language and Literature, 2024)
Some people may misunderstand when communication and fail to obey the maxim that is called flouting maxim. Grice (1975) proposed four types of flouting maxims, they are flouting maxim of quantity, flouting maxim of quality, flouting maxim of relevance, and flouting maxim of manner. People who disobey the maxims can be found in creating humor. In this study, conversation in creating humor became a data source, and Stand Up Comedy Minangkabaunese Rin Hermana and American K-Von were chosen to be analyzed. The purpose of this study is to find out what type of maxim they flouted the most and the differences on both of the Stand Up Comedy. The method of this research is descriptive research. It is found that there were total of 32 utterances that flout the maxim. The results show that Stand Up Comedy Americans flout the maxim the most with 18 utterances while Minangkabaunese with 14 utterances. It is also found that the differences in flouting maxim of both of the Stand Up Comedy show that in Minangkabaunese Rin Hermana flouts maxim of quantity and manner with the highest number of 7 and 5 utterances while Flouting maxim of quality and relevance rarely appeared with 2 and 0. American K-Von flouts maxim of quality and quantity the most with the highest number of 8 and 5 utterances while flouting maxim of manner and relevance with number of 4 and 1 utterances.